Crowdfunding Practices and the Comparison to Fundraising and the Dispute Resolution - Martedjo, Wagiman; Izzulhaq, Muhammad Luthfi Reza (Faculty of Law, Universitas Jenderal Soedirman, 2022)
The practice of ‘crowdfunding’ and ‘fundraising’ by the community sometimes leads to abuse. Judging from the parties, namely the ‘Fundraising Platform’ and ‘Promotion’ and’ Donors’. This article answers three things: first, what if the donor wants to know the use/distribution of the funds? second, what if there is a dispute and its resolution? and third, what actions Donors can take to obtain information from the Promotion? The normative juridical method is used with two flatform models to be compared and analyzed. Using the comparative method in several countries, the transparency and accountability of the information provided is also recorded. Finally, an investigation is carried out if there is a dispute between the Donor and the Beneficiary/Collector, and how the dispute is resolved. Conclusion: First, the implementation of crowdfunding varies, some are specifically regulated but in general they are regulated in a scattered manner. The latter applies in Indonesia. Second, the right of the donor to know information regarding the transparency of its distribution as long as it does not involve confidential information. Donors can request information not from online crowdfunding/online fundraising but from the Campaigner. Third, dispute resolution between the Donor and the Campaigner can be carried out in the realm of information disputes with two stages of dispute resolution, namely: the litigation stage through Mediation and Adjudication and the litigation stage, through the District Court or State Administrative Court.Keywords: Crowdfunding; Fundraising; Dispute; Non-Litigation; Litigation